Motion Assessment for Accelerometric and Heart Rate Cycling Data Analysis - Charvátová, Hana; Procházka, Aleš; Vyšata, Oldřich (Sensors (Basel, Switzerland), 2020)
Motion analysis is an important topic in the monitoring of physical activities and recognition of neurological disorders. The present paper is devoted to motion assessment using accelerometers inside mobile phones located at selected body positions and the records of changes in the heart rate during cycling, under different body loads. Acquired data include 1293 signal segments recorded by the mobile phone and the Garmin device for uphill and downhill cycling. The proposed method is based upon digital processing of the heart rate and the mean power in different frequency bands of accelerometric data. The classification of the resulting features was performed by the support vector machine, Bayesian methods, k-nearest neighbor method, and neural networks. The proposed criterion is then used to find the best positions for the sensors with the highest discrimination abilities. The results suggest the sensors be positioned on the spine for the classification of uphill and downhill cycling, yielding an accuracy of 96.5% and a cross-validation error of 0.04 evaluated by a two-layer neural network system for features based on the mean power in the frequency bands 〈 3 , 8 〉 and 〈 8 , 15 〉 Hz. This paper shows the possibility of increasing this accuracy to 98.3% by the use of more features and the influence of appropriate sensor positioning for motion monitoring and classification.
Keywords: Software; software; Signal Processing, Computer-Assisted; accelerometers; Cell Phone; mobilní telefon; Motion; Humans; Support Vector Machine; Algorithms; rozpoznávání automatizované; support vector machine; neuronové sítě; počítačové zpracování signálu; Heart Rate; machine learning; Neural Networks, Computer; lidé; Models, Statistical; reprodukovatelnost výsledků; pohyb těles; cyklistika; classification; motion monitoring; fitness náramky; srdeční frekvence; Reproducibility of Results; Fitness Trackers; akcelerometrie; Pattern Recognition, Automated; Bicycling; algoritmy; Bayesova věta; Accelerometry; statistické modely; multimodal signal analysis; Exercise; computational intelligence; cvičení; Bayes Theorem